2008
DOI: 10.1590/s0103-64402008000200012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dental wear, stabilization appliance and anterior tooth reconstruction on mandibular movements during speech

Abstract: This study described changes in mandibular movements during pronunciation of /m/ and /s/ sounds in Portuguese, in patients presenting dental wear before and after appliance insertion and tooth reconstruction. Subjects were divided into a control group of dentate patients and an experimental group of patients with incisal tooth wear due to bruxism. A magnetic jaw tracking device measured the jaw opening, and translations to left and right sides of the mandible during pronunciation of phonemes. Evaluations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…In this study, before the beginning of the treatment, mandibular movements in subjects with bruxism averaged 43.69 mm for mouth opening, 8.28 mm for left laterotrusion, and 8.17 mm for right laterotrusion. The increase in all mandibular movements after splint treatment established in this study was confirmed in similar studies in asymptomatic subjects, as well as in subjects with bruxism ( 12 ) and TMD ( 20 , 21 ). In this study, the highest increase in mandibular movements was found for mouth opening, which is consistent with the research by Serrano et al ( 12 ) and Katyayana et al ( 20 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this study, before the beginning of the treatment, mandibular movements in subjects with bruxism averaged 43.69 mm for mouth opening, 8.28 mm for left laterotrusion, and 8.17 mm for right laterotrusion. The increase in all mandibular movements after splint treatment established in this study was confirmed in similar studies in asymptomatic subjects, as well as in subjects with bruxism ( 12 ) and TMD ( 20 , 21 ). In this study, the highest increase in mandibular movements was found for mouth opening, which is consistent with the research by Serrano et al ( 12 ) and Katyayana et al ( 20 ).…”
Section: Discussionsupporting
confidence: 87%
“…The increase in all mandibular movements after splint treatment established in this study was confirmed in similar studies in asymptomatic subjects, as well as in subjects with bruxism ( 12 ) and TMD ( 20 , 21 ). In this study, the highest increase in mandibular movements was found for mouth opening, which is consistent with the research by Serrano et al ( 12 ) and Katyayana et al ( 20 ). The initial values of condyle displacement at mouth opening approach the values in asymptomatic patients from previously published studies ( 22 , 23 ) only after the occlusal splint treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…During speech, the mandible moves rapidly in the sagittal plane with frequent reversals in direction, and the trajectories can vary with the production of different consonants and vowels and with changes to the anterior teeth. [3][4][5] The medial pterygoid muscle (MPT), active in mandibular closing, and the lateral pterygoid muscle (LPT), active in mandibular opening, are critically important muscles in mastication, and are also likely to be two key contributors to the control of mandibular movements in speech. First, of the jaw muscles, the LPT is anatomically the best oriented to generate horizontal force vectors on the mandible in the sagittal plane, [6][7][8] and the superior, anterior, and medial orientation of each MPT 8,9 means that it can act synergistically with the LPT to provide the rapid reversals in mandibular direction in the sagittal plane during speech, and as well to help stabilise mandibular position to allow the lip and tongue muscles to operate during speech.…”
Section: Introductionmentioning
confidence: 99%
“…During speech, the mandible moves rapidly in the sagittal plane with frequent reversals in direction, and the trajectories can vary with the production of different consonants and vowels and with changes to the anterior teeth 3–5 . The medial pterygoid muscle (MPT), active in mandibular closing, and the lateral pterygoid muscle (LPT), active in mandibular opening, are critically important muscles in mastication, and are also likely to be two key contributors to the control of mandibular movements in speech.…”
Section: Introductionmentioning
confidence: 99%